Understanding the journey and decision-making process of doctors throughout their career - Makhal, Manabendra; Ray, Pradip Kumar; Bhattacharya, Sampa Ray; Mandal, Pranab; Layek, Avik Kumar (Asian Journal of Medical Sciences, 2022)
Background: Often, we perceive healthcare from the patient’s point of view. Very seldom do, we think about the doctors, pillars of our health-care system. They have to overcome the journey and faced challenges before fully established. Aims and Objectives: This study aims to explore this area on the perception of doctors about their career, the support they desire and the challenges they face to establishment of their private clinical practices. Materials and Methods: The data were collected from doctors using questionnaires circulated through digital platform during COVID-19 pandemic situation for cross-sectional study. Cluster followed by snowball sampling method was followed to collect the data using two different Google form questionnaires for doctors completed under-graduation and completed postgraduation/super-specialty. Chi-square analysis was used to assess the frequency count variables. Results: The millennial as well as senior doctors have securing financing the highest rank overall as the major challenge, they faced before starting a clinic. Conclusion: Decision-making process of doctors is very complex and dynamic influenced by different factors throughout their career. Factors such as securing post-graduation, securing finance and procuring equipments for the establishment of clinics were found to influence career decision.